Prohibition of Fraud and Cheating in Business According to the Hadith - Desi Endang Maisuri; Putri Alfia Halida; Faridatul Jannah (Taqriri: Journal of Al-Hadith Science Studies, 2026)
This study discusses the prohibition of fraud and deception in business activities based on the sayings (hadiths) of the Prophet Muhammad ﷺ. In Islam, business practices are not merely profit-oriented but must also be founded upon the values of honesty, justice, and trustworthiness. The Prophet’s hadiths explicitly forbid all forms of fraud (gharar) and deception (tadlis), such as concealing product defects, falsifying information, and manipulating weights and measures. These prohibitions aim to uphold economic justice, protect consumer rights, and foster trust in business transactions. This study emphasizes that honesty is the fundamental basis for achieving blessings in trade. Honest business practitioners gain both divine blessings and public trust, whereas those who engage in deceit lose such blessings and incur the Prophet’s condemnation. Thus, the hadiths provide a strong moral and ethical foundation for establishing fair, transparent, and integrity-based business practices within the Islamic economic system.